(untitled) (Marketing Journal, 2025)
The use of IT technologies in tourism development plays a crucial role in increasing efficiency, improving service quality, and creating a comfortable environment for travelers. Artificial intelligence, Big Data, IoT, and blockchain technologies help automate hotels, transportation, excursions, and payment systems. 80 This ensures fast, secure, and personalized services for tourists. The centralization and integration of tourism services through digital platforms contribute to the innovative growth of the industry.